Expression of cyclo-oxygenase-2 and yap/taz in hepatocellular carcinoma in untreated and treated hepatitis C virus patients - Sweed, Dina; Abd-Elbary, Aya; Sweed, Eman; Mosbeh, Asmaa; Moaz, Inas; Yassein, Taha; Elmashad, Shereen (Polish Journal of Pathology, 2022)
The pathogenesis of hepatitis C virus (HCV)-related hepatocellular carcinoma (HCC) differs according to whether prior treatment with interferon (IFN) vs. direct-acting antiviral agents (DAAs) was administered. Cyclo- oxygenase-2 (COX-2), yes-associated protein 1 (YAP), and transcriptional co-activator with PDZ-binding motif (TAZ) play a crucial role in hepatocarcinogenesis. However, their roles in untreated or treated HCV-related HCC development have not been clarified. Therefore, we performed an immunohistochemical study and stained tissue from 83 HCV-related HCC cases using antibodies against COX-2, YAP, and TAZ and correlated their expression with the clinicopathological characteri stics and survival data. The cases were subdivided into 3 groups based on prior HCV treatment. In the 3 groups, COX-2 was significantly higher in HCC tissue compared with adjacent non-tumour liver tissue. However, the expression of YAP/TAZ was not significantly different between HCC and adjacent non-tumour tissue. We further grouped HCC cases into YAP+/TAZ+ and YAP–/TAZ– cases. In the YAP+/TAZ+ cases, COX-2 was significantly associated with tumour size, tumour multifocality, and late pathologic stage. No significant difference was observed in COX-2 and TAZ expression as a result of IFN or DAA treatment; however, YAP was significantly higher in IFN-treated HCC. Cyclo-oxygenase-2 overexpression may play a role in late HCC development, while YAP/TAZ could play an early role in HCC progression. Sustained expression of combined YAP/TAZ could mediate the poor prognostic role of COX-2.